Corporate elites and the reform of public education - Gunter, Helen ca. 20./21. Jh; Hall, David ca. 20./21. Jh; Apple, Michael W. 1942- (Policy Press, 2017)
Leading scholars combine theory and case studies to reveal how elite corporations are increasingly influencing how public education provision and services are delivered across the world